Preoperative embolization of head and neck tumors: a systematic review and meta-analysis - Zhen Long; Yu-Hui Su; Jing-Bin Zhu; Qi-Sen Yao; Zhen Feng; Peng-Yu Chen; Yuan-Feng Liang; Fu Zhu; Yu Ning (World Journal of Surgical Oncology)
Abstract Purpose Preoperative embolization is a widely recognized adjunctive treatment for highly vascular head and neck tumors; however, there is still no consensus regarding its efficacy and safety. Our study aims to address this issue through a meta-analysis. Methods A comprehensive search was conducted in the PubMed, Embase, Web of Science, and Cochrane databases to identify relevant literature on preoperative embolization for head and neck tumors up to March 2025. Randomized controlled trials, cohort studies, and case-control studies involving embolization and non-embolization groups were included. Eligible studies were selected for meta-analysis to estimate intraoperative blood loss, operative time, and postoperative complications. Data were analyzed using Review Manager 5.4 software. Results A total of 30 studies met the inclusion criteria, including 7 randomized controlled trials and 23 cohort studies, encompassing a total of 1,039 patients. Preoperative embolization reduced estimated blood loss. The estimated blood loss was 456 ml in the embolization group compared to 516 ml in the non-embolization group (Standard Mean Difference = -0.67; 95% CI: -1.02 to -0.32; P = 0.0002). Preoperative embolization was associated with increased surgical resection time. The mean resection time was 312 min in the embolization group and 305 min in the non-embolization group (Standard Mean Difference = -0.66; 95% CI: -1.21 to -0.12; P = 0.02). Preoperative embolization did not reduce postoperative complications (Odd ratio = 1.06; 95% CI: 0.42, 2.70; P = 0.90). Conclusions Compared with surgery without preoperative embolization for head and neck tumors, preoperative embolization appears to reduce intraoperative estimated blood loss and increase surgical resection time; however, it does not significantly reduce incidence of complications.